Poor control of pain increases the risk of depression: a cross-sectional study - Junjian Zeng; Junjian Zeng; Zhiqiang Liao; Zhiqiang Liao; Aiqing Lin; Aiqing Lin; Yu Zou; Yu Zou; Yixun Chen; Yixun Chen; Zhonghua Liu; Zhonghua Liu; et al. (Frontiers in Psychiatry)
BackgroundInadequate pain management not only results in prolonged physical discomfort but also causes a range of psychological and social issues, such as anxiety, depression, social withdrawal, and diminished work performance. This study aims to investigate the relationship between the duration of pain and depression.MethodsThis study utilized data on pain and depression from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2014. Participants with a health questionnaire score ≥10 were considered to have depressive symptoms. Weighted univariate, multivariate logistic regression analysis, sensitivity analysis, and restricted cubic spline (RCS) analysis were used to examine the relationship between pain duration and the risk of depression. Additionally, subgroup analysis was conducted to identify potential confounding factors that might affect this relationship.ResultsAmong the 2,248 participants, 442 (19.6%) were diagnosed with depressive symptoms, with an average age of 52 years, 69% of whom were female. After adjusting for all confounding factors, our results show a significant association between pain duration (in months) and depression. Individuals in the highest quartile of pain duration had a 154% higher likelihood of developing depression compared to those in the lowest quartile (OR = 3.375, 95% CI 2.329-4.886, P < 0.001), and the trend test was also significant (P for trend < 0.001). The RCS analysis indicated a linear relationship between pain duration and depression (P for nonlinearity = 0.427).ConclusionThis study’s results indicate that inadequate pain control, resulting in extended pain duration, places patients at a higher risk for depression.